Rekonfigurasi POAC untuk Tata Kelola Era Digital: Tinjauan Pustaka Integratif atas Kesenjangan Bentuk–Substansi dalam Manajemen Sektor Publik - Luthfi Azhari; Wildan Maulana Assani Mualim; Muhammad Daffarezel Ramadhan; Pujo Santoso (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2026)
This study aims to synthesize empirical and theoretical literature on the Planning–Organizing–Actuating–Controlling (POAC) framework in public sector management, identify asymmetries among its functions, and propose a reconfiguration of POAC that is relevant to digital and collaborative governance. The study employs an integrative literature review by examining classical management literature, peer-reviewed journals, government regulations, and official governance indicators. Data were analyzed thematically based on the four POAC functions and synthesized across themes, using Indonesia during the 2021–2025 period as the empirical context. The findings reveal that planning and organizing functions have developed relatively well, while actuating and especially controlling remain persistent weaknesses. This condition is reflected in improvements in several formal governance indicators, including the Electronic-Based Government System (SPBE) Index, Indonesia’s ranking in the E-Government Development Index (EGDI), Unqualified Audit Opinions (WTP), and public service compliance ratings. However, during the same period, the Corruption Perceptions Index (CPI) declined. These findings indicate a gap between administrative achievements and substantive outcomes, consistent with the concept of means–ends decoupling in neo-institutional theory. The study contributes by bridging classical management theory with contemporary governance paradigms and proposing a Data-driven, Networked, Adaptive, and Participatory (DNAP) model of POAC. Practically, the results highlight the need to strengthen controlling functions and adaptive leadership to foster more effective, transparent, and outcome-oriented public governance.